A systematic review of applying modern software engineering techniques to developing robotic systems - Pons, Claudia Fabiana
Robots have become collaborators in our daily life. While robotic systems become more and more complex, the need to engineer their software development grows as well. The traditional approaches used in developing these software systems are reaching their limits; currently used methodologies and tools fall short of addressing the needs of such complex software development. Separat-ing robotics‟ knowledge from short-cycled implementation technologies is essential to foster reuse and maintenance. This paper presents a systematic review (SLR) of the current use of modern software engineering techniques for developing robotic software systems and their actual automation level. The survey was aimed at summarizing existing evidence concerning applying such technologies to the field of robotic systems to identify any gaps in current research to suggest areas for further investigation and provide a background for positioning new research activities.